The Effect of Scientific Approach Based on Tutorial Video on Students’ Reading Comprehension of Procedure Text (A Quasi-Experimental Research at Grade VIII of SMPN 4 Kota Bengkulu) - Ahyauddin Ma’id; Azwandi Azwandi; Arono Arono (Universitas Bengkulu, 2018)
This research aimed to find out whether there was any effect of implementation scientific based approach using tutorial video on students’ reading comprehension as a whole and various aspects in procedure text at grade VIII of SMPN 4 Kota Bengkulu. The design was a quasi-experimental research. The sample consisted of 50 students at grade VIII SMPN 4 Kota Bengkulu, 25 students for experiment group and 25 students for control group. The instrument was a reading test which comprised 50 multiple choice questions, the instrument was tried out with r=0,970. The research findings were as follows; (1) Scientific approach based on tutorial video affected students’ whole reading comprehension; (2) scientific approach based on tutorial video affected students’ reading comprehension in various aspects of reading comprehension, namely; finding general information, finding specific information, integrating information, and learning from text. Further study is recommended for other text types.Key Words: Reading Comprehension, Scientific Approach, Tutorial Video